ANALYSIS OF FACTORS INFLUENCING THE LOW COVERAGE OF K6 ANTENATAL VISITS AMONG PREGNANT WOMEN - Ade Zakiya Tasman Munaf; Yuni Ginarsih; Agustina Mar’atus Sholichah (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2026)
Low coverage of K6 antenatal visits remains a concern as it affects the quality of maternal health services and early detection of pregnancy complications. This study aimed to analyze factors influencing the low coverage of K6 antenatal visits among pregnant women. This quantitative observational study used a cross-sectional design with total sampling involving 43 third-trimester pregnant women, conducted from August to October 2025, and data were analyzed using the chi-square test with a significance level of p<0.05. The results showed a significant association between occupation, parity, education, knowledge, accessibility, and husband’s support with the frequency of K6 antenatal visits (p < 0.05), while age, availability of health facilities, as well as perceptions and cultural factors were not significantly associated. Individual, environmental, and social factors play an important role in determining compliance with K6 antenatal visits, indicating the need for comprehensive intervention strategies to improve antenatal care coverage.